The first Malay database toward the ethnic-specific target molecular variation - Fikri, Hashim Halim; Etemad, Ali; Abdul Latif, Ahmad Zubaidi; Merican, Amir Feisal; Baig, Atif Amin; Annuar, Azlina Ahmad; Ismail, Endom; Salahshourifar, Iman; Liza Sharmini, Ahmad Tajudin; Ramli, Marini; Shah, Mohamed Irwan; Johan, Muhammad Farid; et al. (BioMed Central, 2015)
BACKGROUND:The Malaysian Node of the Human Variome Project (MyHVP) is one of the eighteen official Human Variome Project (HVP) country-specific nodes. Since its inception in 9(th) October 2010, MyHVP has attracted the significant number of Malaysian clinicians and researchers to participate and contribute their data to this project. MyHVP also act as the center of coordination for genotypic and phenotypic variation studies of the Malaysian population. A specialized database was developed to store and manage the data based on genetic variations which also associated with health and disease of Malaysian ethnic groups. This ethnic-specific database is called the Malaysian Node of the Human Variome Project database (MyHVPDb).